Scalable multiparty steering using a single entangled photon-pair - Pepper, Alex (2024)
The distribution and verification of quantum nonlocality across a network of users is essential for future quantum information science and technology applications. However, beyond simple point-to-point protocols, existing methods struggle with increasingly complex state preparation for a growing number of parties. Here, we experimentally demonstrate multiparty detection-loophole-free quantum steering, where one party simultaneously steers multiple spatially separate parties, using a multi-qubit state produced from a set of qubits of which only one pair is entangled. We derive loss-tolerant steering inequalities, enabling our experiment to close the detection loophole, and enabling us to show the scalability of this approach to rigorously verify quantum nonlocality across arbitrarily many parties. This provides practical tools for developing the future quantum internet.